PERTANGGUNGJAWABAN PIDANA PARTAI POLITIK mDALAM TINDAK PIDANA PENCUCIAN UANG - , ADI FREDDY BAWAEDA, Prof. Dr. Marcus Priyo G., SH., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A legal entity, a political party is a national organization and established by a group of Indonesian citizens voluntarily based on the similarity of will and ideals to struggle and defend political interests of community members. Flourishing corruption among the political party elite indicates the involvement of the party in money laundering from the result of crime of corruption committed by the party elite. Therefore, this research is aimed at outline the construction of the criminal liability of the political party as a legal entity in the crime of money laundering. The research employed normative legal research method by using secondary data and data of interview results as supporting data. The secondary data and supporting data were interpreted descriptive- analytically to address the existing problem. The supporting data were obtained by communicating directly through interviews with resource persons and respondents previously determined. The research results indicated that the formulation of the regulations of criminal liability of political party as a corporation in money laundering have been started since the enactment of Law No. 15 of 2002 in conjunction with Law No. 25 of 2003 concerning the Crime of Money Laundering, later replaced by Law No. 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering. The three legislations were based on direct corporate liability. Furthermore, political party under the provisions of the prevailing laws were subject of the criminal law. In the future, the regulation of criminal liability of political party still refers to the reformulation of corporate criminal liability.